Prediction of drug-target binding kinetics by comparative binding energy analysis - Ganotra, Gaurav K.; Wade, Rebecca C. (ACS medicinal chemistry letters, 2018)
A growing consensus is emerging that optimizing the drug-target affinity alone under equilibrium conditions does not necessarily translate into higher potency in vivo and that instead binding kinetic parameters should be optimized to ensure better efficacy. Therefore, in silico methods are needed to predict the kinetic parameters and the mechanistic determinants of drug-protein binding. Here we demonstrate the application of COMparative BINding Energy (COMBINE) analysis to derive quantitative structure-kinetics relationships (QSKRs) for the dissociation rate constants (koff) of inhibitors of heat shock protein 90 (HSP90) and HIV-1 protease. We derived protein-specific scoring functions by correlating koff rate constants with a subset of weighted interaction energy components determined from the energy-minimized structures of drug-protein complexes. As the QSKRs derived for these sets of chemically diverse compounds have good predictive ability and provide insights into important drug-protein interactions for optimizing koff, COMBINE analysis offers a promising approach for binding kinetics-guided lead optimization.
Gesehen am 24.09.2019